Tinjauan Hukum Penyalahgunaan Tanah Wakaf oleh Nazhir dalam Sistem Perwakafan di Indonesia - Muhammad Hafez; Rayna Putri Juliasari; Saiva Wulandari; Darma Ista Maulana; Muhamad Shandy Maulana; Yohana Sandi Wijayanti (Pusat Riset dan Inovasi Nasional, 2025)
Waqf is an act of worship that has a social and economic pattern because in the development of Islamic civilisation, from the development of science to its heyday, it cannot be separated from the role of Rasullulah and his companions who continued to struggle to spread Islam throughout the world, one of which was by using the waqf method because the waqf property or object is often used as a centre for the development of science and Islam in ancient times, for example the construction of mosque buildings and financing wars. Because waqf is an act of worship that is highly recommended for every Muslim. In addition, waqf worship is also explained in the Koran that people who endow their assets for the benefit of the ummah who have benefits, the rewards will continue to flow even though the person has died, which makes people flock to carry out waqf worship. However, it is not uncommon for there to be a lot of abuse committed by nazirs, starting from their unprofessional attitude because nazirs are often used as additional income for them to hoard wealth. So it is very important to find a nadzhir as a zakat manager who has a trustworthy nature because actually this waqf must continue to be developed to be more productive and useful, therefore the Indonesian government continues to make efforts to revise the rules regarding nazir because there are still many irregularities committed largely due to weak administrative sanctions and criminal sanctions for them.